ECO-PHILOSOPHIC PICTURE OF THE WORLD IN THE PROBLEMATIC FIELD OF MODERN COGNITION - Eleonora V. Barkova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article substantiates the need to analysis the picture of the world grounded on the basis of eco-philosophy. The author proceeds from the trend of transformation of modern cognition and shift of the leading paradigm. In contrast to followers of the idea that the centre of the modern picture of the world is technologies or synthesis of technologies the article supports the idea that such centre is man and human type of attitude to the world with its links with nature, society and culture. The novelty of this picture of the world is determined by its eco-philosophic foundation and content, which caused the need to revise the content of its categories.